Assessment of Self Care Management and its Associated Factors among Type 2 Diabetes Patients in Mekelle Hospital and Ayder Referral Hospitals, Mekelle City, Tigray, Northern Ethiopia, 2012/13. (Global Journal of Medical Research, 2017)
Abstract not found
Keywords: type 2 diabetic patients; diabetes management; physical exercise